Credit risks and bank share valuation in selected four Asia Pacific countries - Cheng, Fan Fah; Md Nassir, Annuar (Marsland Press, 2014)
The purpose of this paper is to investigate the relationship between the credit risk and the stock valuation response to earnings for commercial banks in Australia, Korea, Malaysia and Indonesia. These four countries have different bank sizes and sovereign rating. This study applies the relevant accounting and financial ratios into regression models and aims to extend the earnings response literature and theory research to banks. This measures the influence of bank-related determinant of risk that affects risk management in Australia, Korea, Malaysia and Indonesia banks. The results show that the credit risk has the information content beyond earnings. This result is consistent with the finding in many other studies which found significant relationship on the Cumulative Abnormal Returns (CAR) and the credit risk with a positive sign. Generally, the credit risk proxy by the Provision for bad and doubtful debts/Incomes in the existing practical literature shows positive relationship among the credit risk and stock abnormal returns. This positive sign is plausible, because with a higher provision for bad and doubtful debts/Incomes and yet achieving the same amount of earnings mean a better operated banks than the other banks.